2006
DOI: 10.1074/jbc.m604292200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Human IgG1s Engineered for Enhanced Binding to the Neonatal Fc Receptor (FcRn)

Abstract: We describe here the functional implications of an increase in IgG binding to the neonatal Fc receptor. We have defined in a systematic fashion the relationship between enhanced FcRn binding of a humanized anti-respiratory sincytial virus (RSV) monoclonal antibody (MEDI-524) and the corresponding biological consequences in cynomolgus monkeys. The triple mutation M252Y/S254T/T256E (YTE) was introduced into the Fc portion of MEDI-524. Whereas these substitutions did not affect the ability of MEDI-524 to bind to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
524
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(550 citation statements)
references
References 46 publications
21
524
3
2
Order By: Relevance
“…These include residues that make direct contact with FcRn, as well as peripheral and non-surface exposed residues that have the potential to modify the interaction surface and/or influence the dynamics of the 250-helix. Indeed, some of these identified positions have been previously investigated, such as within the half-life enhancing mutants YTE, 10 LS (M428L/N434S), 13 AAA (T307A/E380A/N434A), 27 QL (T250Q/M428L) 11 and V308P. 28 In our analysis, we first investigated the role of each residue in silico , and identified the network of interactions mediated by that residue (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include residues that make direct contact with FcRn, as well as peripheral and non-surface exposed residues that have the potential to modify the interaction surface and/or influence the dynamics of the 250-helix. Indeed, some of these identified positions have been previously investigated, such as within the half-life enhancing mutants YTE, 10 LS (M428L/N434S), 13 AAA (T307A/E380A/N434A), 27 QL (T250Q/M428L) 11 and V308P. 28 In our analysis, we first investigated the role of each residue in silico , and identified the network of interactions mediated by that residue (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…1013 The FcRn affinity-enhancing mutants in these studies were identified from phage display coupled with directed mutagenesis, 1416 alanine scanning, 17 or, in select cases, from molecular modeling and rational design. 11,13 The prototypical example of an FcRn affinity-enhancing Fc mutant is the M252Y/S254T/T256E (YTE) mutation which, when incorporated into motavizumab IgG1, is able to extend serum half-life in humans by more than four-fold.…”
Section: Introductionmentioning
confidence: 99%
“…We also present in vivo data in human FcRn-transgenic mice and in cynomolgus monkeys to investigate mechanism of action, and to allow characterization of pharmacokinetics (PK), pharmacodynamics (PD) and safety. The cynomolgus monkey was selected as a suitable species for investigation of the PK, PD and safety of human IgG, and mutants thereof, because human and cynomolgus monkey IgG4 bind comparably to cynomolgus monkey FcRn 26,27 and have similar Fc effector functions. 28 …”
Section: Introductionmentioning
confidence: 99%
“…These mutations are reported to increase the half-life of antibodies in cynomolgus monkey up to 4 fold. 24 We therefore compared mAB-NN in wild-type IgG1 format with mAB-NN in IgG1 with YTE mutations in a multiple-dose cynomolgus monkey study. The molecules were administered once a week for three weeks, followed by a post-treatment observation period.…”
Section: Resultsmentioning
confidence: 99%